Thermal conductivity of copper and silica nanoparticle packed beds. (February 2016) - Elsahati, Muftah; Clarke, Kevin; Richards, Robert
Abstract: We report here thermal conductivity measurements of packed beds of nanoparticles both under vacuum and at ambient pressure and compare those measurements to theoretical predictions. The thermal conductivity measurements of the nanoparticle beds under vacuum were found to be as low as 0.018 W/m °C, among the lowest thermal conductivities of solid materials ever measured. Theoretical predictions agreed with the conductivity measurements under vacuum within experimental uncertainty. In contrast, thermal conductivities measured for nanoparticle beds at ambient pressure were an order of magnitude higher than the measurements under vacuum, and significantly higher than the theory predicted. These results indicate a serious limitation that could impact the use of nanoparticle beds as very low conductivity insulating materials.